High throughput multiplex immunoassays stratify patients according to symptom burden across the anti-Ro positive systemic autoimmune rheumatic disease spectrum - Sarah Dyball; Rudresh Shukla; Anastasia-Vasiliki Madenidou; Maya H. Buch; Ian N. Bruce; Ben Parker (Autoimmunity)
Anti-Ro/SS-A antibodies are prevalent across systemic autoimmune rheumatic diseases (SARDs) and may signify a distinctive phenotype. This study aimed to identify protein biomarkers associated with symptom burden and health-related quality of life (HR-QoL), and use protein-based stratification to identify clinically meaningful clusters and inflammatory pathways implicated. Anti-Ro positive SARD patients were enrolled in a 6-month pilot study. HR-QoL was determined using a patient-reported visual analogue scale, and symptom burden was assessed with the EULAR Sjögren’s Syndrome Patient Reported Index (ESSPRI). Proximity extension immunoassays measured normalized protein expression (NPX) across 92 inflammatory proteins. Linear regression identified proteins linked to patient outcomes. Unsupervised hierarchical clustering of baseline NPX identified patient clusters. Functional protein association networks were visualized using String V.12.0. Diagnostic groups showed no differences in HR-QoL or physician global assessment (PhGA). Poor HR-QoL and high symptom burden correlated with downregulated inflammatory proteins, while PhGA correlated with upregulated proteins. Two distinct clusters were identified; Cluster 1, ‘low expression cluster’ exhibited higher symptom burden and more impaired HR-QoL, while Cluster 2, ‘high expression cluster’ correlated with a higher physician global assessment (PhGA). Key hub proteins included TGF-β1, CXCL-8, and CCL-2. This study identified patient clusters across the Ro-positive SARD, linking symptom burden to specific proteomic profiles. Unraveling novel protein networks associated with symptom burden and poor HR-QoL may identify therapeutic targets, which address patient-reported outcome measures (PROMs) across several disease indications.